2016
DOI: 10.3892/etm.2016.3957
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a novel thyrotropin receptor mutation (V87L) in a Chinese woman with subclinical hypothyroidism

Abstract: Abstract. The thyrotropin receptor (TSHR) gene has been defined as a highly mutable gene. Mutations in the TSHR gene result in either gain or loss of the receptor function. Subclinical hypothyroidism (SH) is a clinical condition defined as an elevated serum TSH level associated with normal free thyroxine and free triiodothyronine. Chronic autoimmune thyroiditis is the most frequent cause of subclinical hypothyroidism in adults. In rare cases, a loss-of-function mutation of TSHR is the cause of SH. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[4,6] The inactivation mutation of TSHR gene has a wide range of clinical and serological manifestations, ranging from severe non-autoimmune hypothyroidism to hyperthyroxemia with normal thyroid function. [7,8] The degree of TSH resistance depends on the severity of receptor function damage caused by mutation and the number of mut alleles. [9] Previous reports have shown that carriers of homozygous or compound heterozygous mutations are more likely to develop congenital hypothyroidism, while subjects with monoallelic heterozygous mutation in the TSHR gene may present with normal thyroid function or subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…[4,6] The inactivation mutation of TSHR gene has a wide range of clinical and serological manifestations, ranging from severe non-autoimmune hypothyroidism to hyperthyroxemia with normal thyroid function. [7,8] The degree of TSH resistance depends on the severity of receptor function damage caused by mutation and the number of mut alleles. [9] Previous reports have shown that carriers of homozygous or compound heterozygous mutations are more likely to develop congenital hypothyroidism, while subjects with monoallelic heterozygous mutation in the TSHR gene may present with normal thyroid function or subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%